Adapting to Climate Change in ECA - Fay, Marianne; Block, Rachel; Carrington, Tim; Ebinger, Jane (World Bank, Washington, DC, 2012)
Contrary to popular perception, Europe and Central Asia (ECA) countries are significantly threatened by climate change, with serious risks already in evidence. The vulnerability and adaptive capacity of ECA countries to climate change over the next two decades will be dominated by socio-economic factors and legacy issues. The next decade offers a window of opportunity for ECA to make its development more resilient to climate change while reaping co-benefits. Some impacts of climate change will likely remain manageable in the short-term but the costs of poorly designed or implemented policies could rise rapidly.